PEMBEDAYAAN MASYARAKAT DALAM PENEGAKAN HUKUM LINGKUNGAN DIKECAMATAN GROGOL KABUPATEN SUKOHARJO (TINJAUAN TERHADAP PELAKSANAAN UNDANG-UNDANG NO. 23 TAHUN 1997 TENTANG PENGELOLAAN LINGKUNGAN HIDUP) - EDDY SURYANTO HP, RAHARJO EKO MULYONO - (Dinamika Hukum, 2011)
ABSTRACTLaw research [done/conducted] by writer [is] data type utilized in this research [is] data sekunder. Data sekunder, [is] data coming from data [is] mode available [by] for example, legislation, document written, formal document, contact or book. As for which is the including data sekundeer in this research [is] cover the legislation, document written and assumed to show from society enableness in straightening of environmental law, bibliography book, report, diary, archives and other. Result of research and solution that society enableness in giving pernyadaran [of] human right will and environment protection representing one unity which [is] not dissociated, and have the character of [is] equiping each other and also the existence of tergantung in [both/scond] accomplishmen [of] the rights. Appreciation by right of basic of human being and right to the healthy and good environment leave for [at] [is] same ground namely convergent protection ground [at] prevention of rights collision. Rights to the healthy and good environment represent the classic basic right and at the same time represent the rights of basic social having the character of [is] equiping each other. In its implementation to society of Sukoharjo and Grogol more emphasizing to things having the character of preventif with the public education strategy as well as giving adjacent to victim of multilation and environment the Indonesia [is] from : [Party/side] Company, Legislative [party/ side]. [Party/ side] Esekutif.